Transcriptome Analysis Revealed the Mechanism by Which Exogenous ABA Increases Anthocyanins in Blueberry Fruit During Veraison - Han, Tianyu; Wu, Wenlong; Li, Weilin (Frontiers in Plant Science, 2021)
Blueberry (Vaccinium spp.) is a popular healthy fruit worldwide. The health value of blueberry is mainly because the fruit is rich in anthocyanins, which have a strong antioxidant capacity. However, because blueberry is a non-model plant, little is known about the structural and regulatory genes involved in anthocyanin synthesis in blueberries. Previous studies have found that spraying 1,000 mg/L abscisic acid at the late green stage of “Jersey” highbush blueberry fruits can increase the content of anthocyanins. In this experiment, the previous results were verified in “Brightwell” rabbiteye blueberry fruits. Based on the previous results, the anthocyanin accumulation process in blueberry can be divided into six stages from the late green stage to the mature stage, and the transcriptome was used to systematically analyze the blueberry anthocyanin synthesis process. Combined with data from previous studies on important transcription factors regulating anthocyanin synthesis in plants, phylogenetic trees were constructed to explore the key transcription factors during blueberry fruit ripening. The results showed that ABA increased the anthocyanin content of blueberry fruits during veraison. All structural genes and transcription factors (MYB, bHLH, and WD40) involved in the anthocyanin pathway were identified, and their spatiotemporal expression patterns were analyzed. The expression of CHS, CHI, DFR, and LDOX/ANS in ABA-treated fruits was higher in the last two stages of maturity, which was consistent with the change in the anthocyanin contents in fruits. In general, six MYB transcription factors, one bHLH transcription factor and four WD40 transcription factors were found to change significantly under treatment during fruit ripening. Among them, VcMYBA plays a major role in the regulation of anthocyanin synthesis in ABA signaling. This result preliminarily explained the mechanism by which ABA increases the anthocyanin content and improves the efficiency of the industrial use of blueberry anthocyanins.